ANALISIS PENGARUH KEMUDAHAN PENGGUNAAN DAN PROMOSI TERHADAP KEPUTUSAN PENGGUNAAN E-WALLET OVO PADA UMKM DI DKI JAKARTA - Hikmah Wati Annisa, (2022)
The rapid development of technology and information has brought about changes in the payment system in Indonesia which can be accessed digitally via E-Wallet. This study aims to determine the effect of ease of use and promotion on decisions to use OVO E-Wallet on MSMEs in DKI Jakarta. The sampling method used is purposive sampling, with a sample of 100 respondents. In collecting respondent data using google form. This research uses Smart PLS 3.3 (Partial Least Square) software for analysis tool. The results of the analysis show that ease of use and promotion have a positive and significant influence on the decision to use OVO E-Wallet on MSMEs in DKI Jakarta.